Evolution of River Characteristics Impact on Post-Flood and Normal Season in Pinang River Basin, Malaysia - Mohd Khairul Amri, Kamarudin; Muhammad Hafiz, Md Saad; Ahmad Shakir, Mohd Saudi; Firdaus, Mohamad Hamzah; Marlia, Mohd Hanafiah; Noorjima, Abd Wahab; Siti Nur Aisyah, Md Bati (2020)
Characterization of river outflow characteristics in the post-flood and normal seasons was carried out in the Pinang River Basin, Penang. Field sampling was performed twice in November 2017 (post-flood) and in March 2019 (normal season). Cross-sectional measurements involving the measurement of river width, river depth and velocity were performed at both sampling times. The objective of this study was to identify the pattern of river discharge in the Pinang River Basin and to assess the relationship between the occurrence of water discharge and other factors for both seasons. The results showed that the average discharge rate for each river after the rainy season was 0.85 m3 /s for the Dondang River, 1.11 m3 /s for the Ayer Itam River and 3.23 m3 /s for the Sungai Pinang. For the normal season, the mean readings were 0.13 m3 /s for the Dondang River, 0.38 m 3 /s for the Ayer Itam River and 0.69 m3 /s for the Pinang River. Subsequent estimates of flood rates during floods were also estimated by estimating an increase in water depth by five meters. As a result of this estimate, the average drainage rate for the Dondang river is 8.58 m3 /s, the Ayer Itam River at 8.12 m3 /s while the Pinang River is 20.68 m3 /s. The results from the correlation statistics analysis showed a very significant reading between river depths and outflow with R2 = 0.85. The relationship between velocity and water discharge shows a reading of R2 = 0.089 which is not significant. Whereas, the relationship between width and discharge shows a R 2 = 0.495 which is significant. It is hoped that this study will provide as much information as possible before the proper steps are taken to prevent future flood events.